Taming Japan's deflation : the debate over unconventional monetary policy - Park, Gene, 1971-; Katada, Saori N.; Chiozza, Giacomo; Kojo, Yoshiko, 1956- (Ithaca : Cornell University Press, 2018)
"Discusses how entrenched monetary policy ideas within the Bank of Japan, protected by policy network, inhibited addressing persistent deflation since its de jure independence of 1998"--
Ideas, networks and monetary politics in Japan -- Deflation, monetary policy responses, and the BOJ -- Monetary politics: interests, ideas and policy networks -- The BOJ worldview and its historical development -- The monetary policy network -- Ideas and monetary policy: a quantitative test -- Monetary policy making 1998-2012 -- Abenomics and the break with the BOJ orthodoxy.
Includes bibliographical references and index.
AAL
Keywords: Nihon Ginkō.; Monetary policy -- Japan; Deflation (Finance) -- Japan; Banks and banking, Central -- Japan; Japan -- Economic policy -- 1989-